Bandeo de cromosomas humanos con extracto crudo de frutas u hojas de papaya - Solís, María María (Revista de Biología Tropical, 2001)
One week old human chromosome preparations were treated with filtrate from one liquefied leaf (53 g) of papaya (Carica papaya) in 100 ml of distilled water, and stained with 1.5 % Giemsa (pH 6.8). Good chromosome banding was obtained after 2 min of treatment. Solutions that have been frozen even for years are effective and the method is cheaper and easier than others.